2021
DOI: 10.1136/gutjnl-2021-325168
|View full text |Cite
|
Sign up to set email alerts
|

Stool microRNA profiles reflect different dietary and gut microbiome patterns in healthy individuals

Abstract: ObjectivesMicroRNA (miRNA) profiles have been evaluated in several biospecimens in relation to common diseases for which diet may have a considerable impact. We aimed at characterising how specific diets are associated with the miRNome in stool of vegans, vegetarians and omnivores and how this is reflected in the gut microbial composition, as this is still poorly explored.DesignWe performed small RNA and shotgun metagenomic sequencing in faecal samples and dietary recording from 120 healthy volunteers, equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 84 publications
1
40
0
Order By: Relevance
“…[ 13 ] Roseburia sp CAG 182 shows higher abundance in healthy vegetarians/vegans compared to omnivores and it is related to lipid metabolism. [ 14 ] Firmicutes bacterium CAG 95 is associated with dietary patterns and its abundance shows a strongly positive correlation with healthy plant‐ or animal‐based foods while less correlation with less healthy plant‐ or animal‐based foods. [ 15 ] In addition, both Firmicutes bacterium CAG 95 and Firmicutes bacterium CAG 110 are associated with the dysregulation of fatty acid metabolism and an inflammatory surrogate GlycA in host.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] Roseburia sp CAG 182 shows higher abundance in healthy vegetarians/vegans compared to omnivores and it is related to lipid metabolism. [ 14 ] Firmicutes bacterium CAG 95 is associated with dietary patterns and its abundance shows a strongly positive correlation with healthy plant‐ or animal‐based foods while less correlation with less healthy plant‐ or animal‐based foods. [ 15 ] In addition, both Firmicutes bacterium CAG 95 and Firmicutes bacterium CAG 110 are associated with the dysregulation of fatty acid metabolism and an inflammatory surrogate GlycA in host.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs (miRNA) are single-stranded, short RNAs that post-transcriptionally regulate gene expression by binding to the 3 untranslated region (UTR) and silencing the target genes (Chopra et al, 2020;Li et al, 2020). They can be detected in the brain, biofluids [urine, cerebrospinal fluid (CSF), and blood], and, more recently, in stool samples (Tarallo et al, 2021). With a growing number of studies elucidating the role of miRNAs in various disease processes, the gut-residing microbes can further modulate miRNA expression and regulate host pathophysiology.…”
Section: Chronic Gut-inflammation and Intestinal Barrier Dysfunction ...mentioning
confidence: 99%
“…Astonishingly, the number of bacteria present in our body shows a nearly equal ratio to human cells (1.3:1). It boasts immense metabolic capabilities as the gut-microbiota may contain up to 23 million genes -a number that dwarfs the human genome (Claesson et al, 2009;Sender et al, 2016;Tierney et al, 2019). Since gut-residing bacteria are vital for host survival, understanding their influence can broaden the horizon for diagnosis and therapy for complex multifactorial diseases, including neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated direct links between faecal miRNA profiles, diet, and gut microbial composition. 62 , 63 Teng and colleagues showed that miRNAs found in edible plants, enclosed in derived exosome-like nanoparticles, can be taken up preferentially by bacteria issuing changes in the microbiome composition, growth, and localisation. 62 Exogenous miRNAs from plants may also be taken up by the host and accumulate in serum and tissue.…”
Section: Mechanisms By Which Mirna-microbiota Interactions May Lead T...mentioning
confidence: 99%